Penguatan Citra Madrasah Melalui Budaya Organisasi Dan Peran Komite Madrasah Di Pedesaan Pada Era Disrupsi - Tubagus Syihabudin; Tihami; Agus Gunawan (STAI Terpadu Yogyakarta, 2023)
Madrasah are an alternative for Muslims in Indonesia to entrust the best educational process for their children. The current development of madrasah faces problems, including weak organizational culture, the ineffectiveness of the role of madrasah committees, and the unimproved image of madrasah. This study analyzed the strengthening and influence of leadership transformation, work culture, and the madrasah committee's role in the Madrasah Tsanawiyah's picture. This study uses a quantitative method with a survey approach. The sample selection used a simple random sample of teachers and guardians of Madrasah Tsanawiyah in Anyer, Serang District. Primary data comes from interviews, while secondary data comes from documentation. Data analysis used multiple regression using SPSS software version 25.00. The results showed that partially strengthening the image of the madrasah was influenced by organizational culture, enhancing the image of the madrasah was influenced by the role of the madrasah committee, and simultaneously strengthening the image of the madrasah was influenced by organizational culture and the role of the madrasah committee. This research implies that the stronger the image of the madrasah, the better the organizational culture and role of the madrasah committee.